Intégrer la dimension de genre dans le développement de clusters - Département du commerce, des investissements et de l'innovation; Organisation des Nations Unies pour le développement industriel (ONUDI, 2019)
Keywords: EDI; OFDIG; afrique; approches et analyses; asie; autodétermination; discipline; entrepreneuriat; genre; identités LGBTQIA2+; international; rapports sociaux de sexe; régions géographiques; sciences de la gestion; thématiques; économie; égalité des sexes

Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (UNU-INRA Working Papers, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes

Des lesbiennes en devenir coming-out, loyauté filiale et hétéronormativité chez des descendantes d'immigrant·e·s maghrébin·e·s - Amari, Salima (Cahiers du Genre, 2012)
À partir du cas de lesbiennes d’ascendance maghrébine, de leurs rapports avec leurs familles et de leur éventuel sentiment d’appartenance à la communauté gay et lesbienne en France, cet article traite de l’émergence du sujet dans la configuration complexe que forment les rapports sociaux de sexe, de race, de classe et de sexualité. Il s’appuie sur huit entretiens menés auprès de femmes âgées de 25 à 38 ans. Confrontées aux injonctions paradoxales des normes de coming-out , de loyauté filiale et d’hétéronormativité, ces femmes évoluent dans une ambivalence permanente. Une situation qui permet la construction de sujets tacites, ambivalents et incertains : des lesbiennes en devenir.
Keywords: afrique; algérie; approches et analyses; cours; europe; fem1300; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; maroc; premier cycle; rapports sociaux de sexe; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques